Biomechanical Test Following Removal of a Dynamic Hip Screw: In Vitro Analysis - Freitas, Anderson (Cureus, 2018)
The objective of this study was to evaluate, by means of a static flexural test, the biomechanical parameters necessary for the occurrence of a proximal femoral fracture in a synthetic bone model after the removal of a dynamic hip screw (DHS) and comparing the results obtained with a reinforcement technique using polymethylmethacrylate (PMMA). Twenty synthetic bones made of the same material and from the same manufacturer were used: ten units as the control group (CG), five units as the test group without reinforcement (TG), and five units as the test group with reinforcement (TGR). The biomechanical analysis was performed simulating a fall over the trochanter using a servo-hydraulic machine. In the control group, the assay was performed with its integrity preserved. In the TG and TGR groups, a DHS model was introduced, and the tests were performed as follows: TG after simple removal of the synthesis material, and in the TGR group, after removal of the synthesis material and filling the orifice of the femoral neck with PMMA. All groups presented with a basicervical fracture of the femoral neck. The CG group presented a mean of 935 newtons (N) of maximum load and 7.0 joules (J) of energy for fracture occurrence. TG and TGR groups presented, respectively, a maximum load of 750 N and 1,068 N, and energy of 6.0 J and 7.3 J. According to the one-way analysis of variance (ANOVA), there was no significant difference in flow load (p = 0.16), energy to flow (p = 0.16), stiffness (p = 0.28), maximum load (p = 0.10), and energy to fracture (p = 0.54) between the studied groups. The removal of the DHS implant from the synthetic bone did not present a significant increase of the maximum load and the energy necessary for the occurrence of a fracture with the use of the PMMA reinforcement technique.